Deregulation and the power of private surveillance in markets - Cullen, James P. (Economics and Business Review, 2009)
This paper serves as a brief discussion on the current international financial architecture, and the power afforded to private actors in capital markets. When the term 'private surveillance' is used, it denotes the activities of supervisory bodies which are privately owned, unelected and largely unaccountable to state, national or international authorities. This also encompasses the supervision of market participants which use products that are extraneous to current direct international regulatory structures. This paper is grounded in observational research; it uses observations of capitalist market ideology and its relationship with modern finance, together with brief discussions of market actors, to form a critique of the arrangements that have come to dominate regulation of the free market system. It also reflects the author's position as a lawyer, rather than an economist, and focuses on the regulatory challenges that face Western economies. Liberalized financial markets and the attendant increased capital flows between territories have required a deregulatory drive since the collapse of Bretton Woods. This deregulation is an aspect of the political philosophy referred to as neoliberalism, an ideology founded on the principles of minimum state intervention and highly decentralized and liberalized capital markets. This, in turn, has placed great power in the hands of non-state bodies and the market itself in the overarching framework of financial regulation, in preference to the ethos of state surveillance of financial services, products and capital flows which dominated during the post-war era. With this power comes responsibility for the integrity of the financial system, but this paper will highlight the ambiguous role that orthodox liberal philosophy has demanded of these private bodies, and discuss the implications this has for future regulatory structures. It will also critically analyse the danger that placing such power in the hands of private bodies may generate in terms of potential systemic risk. It will briefly address the experience of less financialized economies and their greater resilience to economic contraction. It will conclude by examining ways in which future regulation of capital markets may be served by moving away from the highly deregulated neoliberal paradigm and moving towards the creation of a more interventionist legal axiom. (original abstract)